Antibacterial and anti-inflammatory effects of PGLa-loaded TiO2 nanotube arrays - Xuan, Bin; Li, Lei; Zhang, Hui; Liu, Zhuojue; Luo, Ruxi; Yang, Wenpeng; Wang, Weili (Frontiers in Chemistry, 2023)
Objectives: This study investigated the antimicrobial effect and anti-inflammatory activities of PGLa-loaded TiO2 nanotube arrays (TiO2 NTs) in osteoblast-like MG-63 cells. Methods: The surface morphology and roughness of three titanium (Ti) substrates (Ti, TiO2 NTs, PGLa-loaded TiO2 NTs) were evaluated by scanning electron microscopy (SEM) and atomic force microscope (AFM). The wettability of three titanium substrates was evaluated by contact angle. Biocompatibility of PGLa-loaded TiO2 NTs were evaluated in MG-63 cells (cell adhesion, proliferation, cytoskeletal evaluation and alkaline phosphatase activity). Spread plate counting method was used to evaluate antibacterial abilities of the titanium substrates. The calcein AM/PI staining evaluated cell viability of MG-63 cells on the substrates with or without proinflammatory factors (TNF-α). Results: The average surface roughness of untreated Ti, TiO2 NTs, PGLa-loaded TiO2 NTs were found to be 135.8 ± 6.4 nm, 300.5 ± 10.5 nm, 348.9 ± 16.9 nm, respectively. The contact angle of the untreated Ti was 77.4° ± 6.6°. TiO2 NTs displayed excellent wettability which of contact angle was 12.1° ± 2.9°. The contact angle of the PGLa-loaded TiO2 NTs was 34.6° ± 4.9°. MG-63 cells on surface of PGLa-loaded TiO2 NTs showed better cell adhesion, proliferation and osteogenic activity. The antibacterial rate of PGLa-loaded TiO2 NTs group significantly increased (84.6% ± 5.5%, p < 0.05). The rate of dead cells on the surfaces of the PGLa-loaded TiO2 NTs with TNF-α decreased significantly (4.49% ± 0.02, p < 0.01). Conclusion: PGLa-loaded TiO2 NTs have multi-biofunctions including biocompatibility, antibacterial and anti-inflammatory properties.